Open your eyes: an essay on color ontology - Roberts, Pendaran (2014)
This essay is an exercise in philosophy. It asks, “what are the colors?”, and ultimately provides a primitivist answer. The essay has four parts. The first is entitled “Stage setting” and has two subparts. In 1.1, I provide an explanation of how we should understand the question of which this essay is concerned. The goal of 1.2 is to provide an adequate taxonomy of views. Part 2 is entitled “Dispositional views” and has three subparts. In 2.1, I argue against appearance dispositional views. In 2.2, I argue against reflectance dispositionalism. Finally in 2.3, I provide a general argument against the colors being dispositions. Part 3 is entitled “Categorical views” and has three subparts. In 3.1, I argue against micro-structuralism. In 3.2, I argue against Cohen’s relationalism. Finally in 3.3, I argue for and defend non-relational primitivism. In the last major section of this essay I look at whether we should give up on the colors actually being instantiated. This section has only one subpart, and in it I reject the argument that the best explanation of mass disagreement about the colors is that irrealism is true.